Effectivity of Injection Sclerotherapy on Early Haemorrhoids Reported to Surgical Outpatient Department (Journal of Armed Forces Medical College, Bangladesh, 2011)
This prospective study was carried out at a Military Hospital over a period of 10 months. Total 96 cases of first degree and early second degree haemorrhoid cases treated by injection sclerotherapy were included in this study. Among them, first degree haemorrhoids were 60% cases and early second degree haemorrhoids were 40% cases. The highest number of patients was in 3rd and 4th decade (81%). After adequate bowel preparation, under proctoscopy three positions of haemorrhoids were identified. By a Gabrial syringe 5% phenol in olive oil (3-5 ml) was injected in the submucosa of the pedicle of each haemorrhoid. The patients were followed up monthly for six months. All the patients were presented with painless per rectal bleeding. Constipation was present in 89% cases. Satisfactory result was observed in 60% cases and out of them 40 cases were having first degree haemorrhoids and rest of the cases were having early second degree haemorrhoids. Second dose of injection was required in 38 cases and third dose of injection was required in 32 cases. Out of 38 patients who received second dose of injection, only 6 patients had satisfactory outcome and almost all but one patient who received third dose of injection showed unsatisfactory result. Reported method is easy, convenient, cheap and effectively practicable at outdoor level.Key words: Haemorrhoid; sclerotherapy; satisfactory outcome DOI: 10.3329/jafmc.v6i2.7270JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.25-27